Konkursna procedura na deržavnìj službì v Ukraïnì: vprovadžennâ êvropejsʹkogo dosvìdu - Ânûk, Natalìâ (Lʹvìvsʹkij nacìonalʹnij unìversitet ìmenì Ìvana Franka, 2021)
This article is a complex research of the competitive procedure of civil service of Ukraine. This research contains a chain of theoretical principles and recommendations enunciated as a result of the comparative legal analysis of the legislation of Ukraine and the legislation of the European Union holding competition procedures. This article substantiated the determination of a definition, principles and structure of the competitive procedure of the civil service on the basis of the systematical structural and functional analysis effective legislation of Ukraine. The experiences of European countries have proven that competition is an effective way to form a politically impartial and professional civil service. The competitive procedures are a way to determine the best candidate for a civil service position. The competitive procedure this qualification of business, personal, competence qualities of each candidate for civil service, which is regulated by administrative legislation, and competitive procedure makes it possible to identify the most professionally trained to fill a vacant civil service position. This procedure is characterized by: subjects, time limits, stages and principles. The basic principles of the competition procedure are: legality, openness and publicity, non discrimination, competition, equal treatment of candidates. Author described the organizational and legal basis of the competition as a way filling in positions of civil service in the executive branch. The legislation of Ukrainian established the important stages of the competition: announcement of the civil service competition is placed on the Unified portal of civil service vacancies; testing, solving situational tasks in a written form (categories “A”and “B”, interviews, determining the results of the competition and compiling a rating of candidates, the final results of the competition and person who has won the competition; publication of the results of the competition on the Unified portal of civil servicevacancies. The decision on the results of the competition may be appealed to the Administrative Court. In Ukrainian was formed the competition two types of commissions – Competition Commission of the senior corps of the civil service (for positions of category “A”) andcompetition commissions for positions of other categories. In 2020 humanity first encountered a pandemic caused by the coronavirus COVID-19. In March last year the Government of Ukraine introduced quarantine and competition procedures for the civil service was stopped. The suspension of the competition caused controversy in society. In a March of this year, Ukrainian legislation was amended. After the change of the legislation on the civil service, certain stages of the competition can be held remotely using video communication. It is necessary to improve national legislation order to ensure the objectivity of competition in video communication, as well as to ensure the participation of representatives of public organizations and experts in competition scommissions. Research and analysis of the legislation of some European countries, Poland, Latvia, Lithuania, Estonia and other countries, contributes to the continuous improvement of national legal regulation of competition in the civil service and ensuring open competition
Keywords: European experience; competition commissions; hiring on the civil service; equal treatment of candidates; êvropejsʹkij dosvìd; konkursnì komìsìï; prijnâttâ na deržavnu službu; rìvnìstʹ kandidatìv